Innovations in the Treatment of Atopic Dermatitis: Integration of Targeted Therapies and Comprehensive Care - Perzynska, Jagienka; Podkościelna, Jaśmina; Kasterka, Natalia; Bagińska, Weronika; Ryszkowska, Kamila; Pawelec, Natalia; Purska, Aleksandra; Krzyżowska, Kinga (Quality in Sport, 2026)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with a complex pathogenesis involving epidermal barrier dysfunction, immune dysregulation, microbiome imbalance, and environmental and psychosocial factors. Recent advances have led to the development of targeted therapies that have significantly improved disease management, particularly in moderate-to-severe AD. Biologic agents and Janus kinase (JAK) inhibitors effectively modulate key immune pathways, while topical calcineurin inhibitors remain important steroid-sparing options. Emerging microbiome-based therapies and holistic approaches further expand therapeutic possibilities by addressing additional disease mechanisms and contributing factors. Despite these advances, challenges such as cost, accessibility, and the need for long-term safety data persist, highlighting the importance of personalized and integrated treatment strategies.